Evolutionary divergence in life history traits among populations of the Lake Malawi cichlid fish Astatotilapia calliptera. Issue 20 (12th September 2017) - Parsons, Paul J.; Bridle, Jon R.; Rüber, Lukas; Genner, Martin J.
Abstract: During the early stages of adaptive radiation, populations diverge in life history traits such as egg size and growth rates, in addition to eco‐morphological and behavioral characteristics. However, there are few studies of life history divergence within ongoing adaptive radiations. Here, we studied Astatotilapia calliptera, a maternal mouthbrooding cichlid fish within the Lake Malawi haplochromine radiation. This species occupies a rich diversity of habitats, including the main body of Lake Malawi, as well as peripheral rivers and shallow lakes. We used common garden experiments to test for life history divergence among populations, focussing on clutch size, duration of incubation, egg mass, offspring size, and growth rates. In a first experiment, we found significant differences among populations in average clutch size and egg mass, and larger clutches were associated with smaller eggs. In a second experiment, we found significant differences among populations in brood size, duration of incubation, juvenile length when released, and growth rates. Larger broods were associated with smaller juveniles when released and shorter incubation times. Although juvenile growth rates differed between populations, these were not strongly related to initial size on release. Overall, differences in life history characters among populations were not predicted by major habitat classifications (Lake Malawi or peripheral habitats) or population genetic divergence (microsatellite‐based F ST ). We suggest that the observed patterns are consistent with local selective forces driving the observed patterns of trait divergence. The results provide strong evidence of evolutionary divergence and covariance of life history traits among populations within a radiating cichlid species, highlighting opportunities for further work to identify the processes driving the observed divergence. Abstract : During the process of adaptive radiation, species can diverge in life history traits as well as habitat use, diet, and behaviour. Here, we provide evidence of divergence in life history traits within Astatotilapia calliptera, a species within the Lake Malawi cichlid fish radiation. These results suggest that life history divergence could take a role in cichlid speciation.